Comparative productivity of the Brahman and some indigenous Sanga and Bos indicus breeds of East and Southern Africa - Hetzel, D.J.S. (1988)
Major evaluation studies involving cattle breeds indigenous to eastern and southern Africa and their crosses are summarised. Comparative productivity of the Boran, Mashona, Tuli, Barotse, Angoni and Africander relative to the Brahman in designated high- and low-performance environments free of the tsetse fly were derived. In general, the indigenous breeds are highly productive, largely due to high reproductive rates. The most productive breeds in the high- and low-performance environments were the Tuli and Mashona, respectively. The Africander was the least productive breed in both environments. Breed-environment interactions were apparent. Crossing between indigenous breeds and Bos taurus or Brahman did not improve maternal performance above the most productive indigenous breeds. However, the growth rate of progeny increased. Thus crossbreeding programmes using the superior indigenous breeds as dams and exotic Bos taurus or Bos indicus as terminal sire breeds are recommended where controlled mating is feasible. The development of a composite breed is currently being evaluated in Botswana. There is a need to evaluate crosses between the most productive Sanga breeds, e.g. Tuli and Mashona, and Bos indicus breeds, e.g. Brahman and Boran, especially in stressful environments where better adaptation is advantageous. Furthermore, it is suggested that future evaluations should include not only production traits but also adaptive traits such as parasite resistance and heat tolerance, and ideally should incorporate several nutritional levels, so that results can be extrapolated more readily to other environments.